2014
DOI: 10.1021/es4057467
|View full text |Cite
|
Sign up to set email alerts
|

Highly Elevated Serum Concentrations of Perfluoroalkyl Substances in Fishery Employees from Tangxun Lake, China

Abstract: Increasing production and use of per-and polyfluoroalkyl substances (PFASs) has been reported from China, and a few studies have shown there are subpopulations in China with high and increasing exposure to these chemicals. In this paper, we present a comprehensive exposure assessment of PFASs in fishery employees from Tangxun Lake, China. Exceptionally high serum concentrations of C4 to C12 PFASs were observed in fishery employees (n = 39, median perfluorooctanesulfonic acid (PFOS) 10 400 ng/mL) compared to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 60 publications
7
123
1
Order By: Relevance
“…23 Li et al found a positive correlation between PFOS in urine and serum samples but none for PFOA. 39 In this study, PFOS, PFOA, and PFHxS in the paired serum and urine samples showed significant linear correlations with each other (Table S8).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 Li et al found a positive correlation between PFOS in urine and serum samples but none for PFOA. 39 In this study, PFOS, PFOA, and PFHxS in the paired serum and urine samples showed significant linear correlations with each other (Table S8).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…PFAA concentrations in indoor dust from the occupational settings and the workers' homes were much higher than samples collected from other places in this study and those from areas not affected by the production facility. 23,33,40 Generally, the PFOS, PFOA, and PFHxS isomer profiles in indoor dust from the worker's houses were similar to those from the facility, indicating that the PFAAs in the workers' houses could have originated from the manufacturing plant. In the TSP samples collected from the manufacturing facility, the geometric mean PFOS, PFOA, and PFHxS concentrations were 2.29, 24.1, and 0.69 ng/m 3 , respectively.…”
Section: Environmental Science and Technologymentioning
confidence: 84%
“…Contrastingly, PFOS concentrations varied more than 2 orders of magnitude between Xiaoqing River (AM 2.097 ng/L) and Tangxun Lake (AM 242.7 ng/L). The substantially elevated concentrations of PFOS in Tangxun Lake have previously been attributed to the direct release from POSF production sources, 23,24 whereas the contamination profile of PFOS along Xiaoqing River was likely influenced by multiple diffuse sources. 32 Although concomitantly high concentrations of F-53B and PFOS have been observed in wastewater from metal plating facilities in China, 14 the differences in F-53B to PFOS ratios between Xiaoqing River and Tangxun Lake indicate that differences in their production sources may also lead to variability in their emission patterns and geographical distribution.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The ERAs for PFOS and PFOA in the sediments in PRE seemed to be negligible due to the relatively low RQ and the phase out of the production of the compounds. However, the potential environmental problem of the short-chain PFASs brought about by the expected increasing usage and production of PFOS substitutes such as PFBS and PFHxS should warrant further study because these compounds have been found in human blood in China with high concentrations (Zhou et al, 2014).…”
Section: Environmental Risk Assessment Of Pfos and Pfoamentioning
confidence: 99%